Becoming a Presidential Candidate: Social Media Following and Politician Identification. Issue 5 (3rd September 2019) - McLaughlin, Bryan; Macafee, Timothy
Abstract : Political candidates increasingly use social media to tell their stories, share their thoughts and feelings and chronicle an unfolding election. We argue that the concept of identification—the process through which an audience member cognitively assumes the perspective of a media personality—can help illuminate how online campaigns can increase citizen support. This study employed a two-wave survey with a U.S. national sample conducted prior to the 2016 presidential election. Results of our analysis support our expectations that following Hillary Clinton and Donald Trump on social media leads to increased identification with that candidate, which then affects candidate support.